Mutual agreement procedure provided for in Directive 2017/1852 as a remedy for the problem of double taxation in the European Union - Moskal, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In order to address the negative consequences of double taxation of the same income or capital belonging to a EU citizen, bi- and multilateral tax treaties have been concluded between the Member States. The EU legislator has enacted legislation introducing measures such as Directive 2003/49/EC, Directive 2011/96/EU and the EU Arbitration Convention to counteract the adverse effects of double taxation. Considering the imperfections in the previous procedures, the Council of the EU has issued Directive 2017/1852 on double taxation dispute resolution mechanisms in the EU, aiming to eliminate the existing shortcomings and to create a harmonized framework for dispute resolution. The aim of this article is to present the phenomenon of double taxation in the EU, to identify the shortcomings of the current mechanisms and to conduct a comprehensive analysis of the procedure provided for in Directive 2017/1852.
Keywords: double taxation; EU law; Directive 2017/1852